2021
DOI: 10.21273/hortsci16074-21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Spraying with Different Concentrations of Selenium Fertilizer on the Development, Nutrient Absorption, and Quality of Citrus Fruits

Abstract: Selenium (Se) fertilizer has a good effect on many field crops, but there are few reports on the application of Se fertilizer on citrus. We investigated the effects of 0 mg/L (CK, water treatment), 50 mg/L, 100 mg/L, 150 mg/L, and 200 mg/L sodium selenite aqueous solutions on the growth, nutrition, and fruit quality of 15-year-old citrus unshiu (Citrus reticulata Blanco cv. Succosa). The results showed that a low concentration of Se fertilizer promoted the growth and development of the citrus plan, and a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
3
6
1
Order By: Relevance
“…Meanwhile, the fruit shape index (H/D) and vitamin C content of Se-rich navel oranges were higher than those of ordinary navel oranges, but the titratable acid content was lower than that of ordinary navel oranges ( Table 1 ). This is consistent with the findings of Wen et al (2021) , who demonstrated that exogenous application of Se fertiliser (150 mg⋅L –1 Se) significantly promoted citrus growth and development, increasing single fruit weight, horizontal and longitudinal diameter, and vitamin C content, while reducing acidity ( p < 0.05). This is mainly attributed to the fact that the application of Se fertiliser promotes an increase in chlorophyll content in the plant body and promotes photosynthesis ( Zhang M. et al, 2014 ; Wen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Meanwhile, the fruit shape index (H/D) and vitamin C content of Se-rich navel oranges were higher than those of ordinary navel oranges, but the titratable acid content was lower than that of ordinary navel oranges ( Table 1 ). This is consistent with the findings of Wen et al (2021) , who demonstrated that exogenous application of Se fertiliser (150 mg⋅L –1 Se) significantly promoted citrus growth and development, increasing single fruit weight, horizontal and longitudinal diameter, and vitamin C content, while reducing acidity ( p < 0.05). This is mainly attributed to the fact that the application of Se fertiliser promotes an increase in chlorophyll content in the plant body and promotes photosynthesis ( Zhang M. et al, 2014 ; Wen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the findings of Wen et al (2021) , who demonstrated that exogenous application of Se fertiliser (150 mg⋅L –1 Se) significantly promoted citrus growth and development, increasing single fruit weight, horizontal and longitudinal diameter, and vitamin C content, while reducing acidity ( p < 0.05). This is mainly attributed to the fact that the application of Se fertiliser promotes an increase in chlorophyll content in the plant body and promotes photosynthesis ( Zhang M. et al, 2014 ; Wen et al, 2021 ). The assimilates of photosynthesis are the material basis of plant cell activity, and the accumulation of photosynthates directly affects a range of metabolic activities ( Matsoukas et al, 2012 ; Wen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A proper dose of Se fertilizer enhances Se accumulation in different plant parts but reduces the accumulation of heavy metals [ 64 ]. The application of Se promotes concentrations of nitrogen, phosphorus, potassium, calcium, and magnesium in citrus leaves [ 99 ] and also increases potassium and calcium concentrations of grape berries [ 100 ]. The nitrogen, potassium, and calcium uptake of wheat seedlings ( Triticum aestivum L.) was enhanced by the application of 5 μM Na 2 SeO 4 but the nitrogen uptake was significantly declined by10 μM Na 2 SeO 4 [ 101 ].…”
Section: Selenium Improves Crop Quality and Resistance To Environment...mentioning
confidence: 99%